Botswana : 2022 Article IV Consultation -Press Release; Staff Report; and Statement by the Executive Director for Botswana. (IMF Staff Country Reports; Country Report ;, 2022)
As of end-2021, Botswana had recovered to its pre-crisis output level thanks to a strong rebound in demand for diamonds, a successful vaccination campaign, and policy support. Fiscal and current account deficits both narrowed sharply, and foreign reserves stabilized but buffers are yet to be fully rebuilt. Inflation exceeded the central bank's medium-term objective range, while unemployment rose close to record highs. Growth in 2022 and beyond is expected to be around potential, while fiscal and external positions are projected to strengthen with more favorable terms of trade and strong fiscal consolidation. Risks to the outlook are associated with the war in Ukraine, the pandemic, and the implementation of fiscal consolidation and economic diversification plans.